Bacillus Calmette–Guérin-Induced Trained Immunity Is Not Protective for Experimental Influenza A/Anhui/1/2013 (H7N9) Infection in Mice - de Bree, L. Charlotte J.; Marijnissen, Renoud J.; Kel, Junda M.; Rosendahl Huber, Sietske K.; Aaby, Peter; Benn, Christine Stabell; Wijnands, Marcel V. W.; Diavatopoulos, Dimitri A.; van Crevel, Reinout; Joosten, Leo A. B.; Netea, Mihai G.; Dulos, John (Frontiers in Immunology, 2018)
Avian influenza A of the subtype H7N9 has been responsible for almost 1600 confirmed human infections and more than 600 deaths since its first outbreak in 2013. Although sustained human-to-human transmission has not been reported yet, further adaptations to humans in the viral genome could potentially lead to an influenza pandemic, which may have severe consequences due to the absence of pre-existent immunity to this strain at population level. Currently there is no influenza A (H7N9) vaccine available. Therefore, in case of a pandemic outbreak, alternative preventive approaches are needed, ideally even independent of the type of influenza virus outbreak. Bacillus Calmette-Guérin (BCG) is known to induce strong heterologous immunological effects, and it has been shown that BCG protects against non-related infection challenges in several mouse models. BCG immunization of mice as well as human induces trained innate immune responses, resulting in increased cytokine responses upon subsequent ex-vivo PBMC restimulation. We investigated whether BCG (SSI-Denmark)-induced trained immunity may protect against a lethal avian influenza A/Anhui/1/2013 (H7N9) challenge. Here we show that isolated splenocytes as well as peritoneal macrophages of BCG-immunized BALB/c mice displayed a trained immunity phenotype resulting in increased innate cytokine responses upon ex-vivo restimulation. However, after H7N9 infection, no significant differences were found between the BCG immunized and the vehicle control group at the level of survival, weight loss, pulmonary influenza A nucleoprotein staining, or histopathology. In conclusion, BCG-induced trained immunity did not result in protection in an oseltamivir-sensitive influenza A/Anhui/1/2013 (H7N9) challenge mouse model.